Peran Kepemimpinan Kepala Desa Dalam meningkatkan Kedisiplinan Kerja Perangkat Desa di Desa Cicangkanghilir-Cipongkor Bandung Barat - Hofifah, Hofifah; Rojak, Abdul (STMIK Dharmapala Riau, 2026)
This study aims to understand the role of the village head in improving the work discipline of village officials at the Cicangkanghilir Village Office. The main focus of the research includes three aspects: the role of the village head in shaping work discipline, the effectiveness of the leadership strategies applied, and efforts to build effective leadership capabilities. This research used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the village head has a real influence on the attitudes and behavior of village officials, encouraging the creation of effective cooperation. The leadership carried out is in accordance with the theory stating that leaders are able to create work harmony in order to achieve productivity. In addition, work discipline has become part of the work culture, reflected in compliance with applicable rules in the village government environment.